The Effect Of Price And Facilities On Customer Satisfaction At Vera Grocery Store, Cengkareng, West Jakarta - Mas'adi, Mahnun; Nuryani, Nuryani (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
The purpose of this study was to determine the effect of price and facilities on customer satisfaction at Toko Sembako Vera, West Jakarta. The method used is quantitative. The sampling technique used the Rao Purba formula and obtained a sample of 96 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are Price has a significant effect on customer satisfaction with a determination coefficient value of 20.0% and the hypothesis test obtained t count> t table or (-4.844> 1.986). Facilities have a significant effect on customer satisfaction with a determination coefficient value of 42.7% and the hypothesis test obtained t count> t table or (8.378> 1.986). Price and facilities simultaneously have a significant effect on customer satisfaction with the regression equation Y = 24.650 + -0.134X1 + 0.495X2. The coefficient of determination value is 53.5% while the remaining 46.5% is influenced by other factors and the hypothesis test obtained a calculated F value > F table or (53.581 > 2.700).